2011
DOI: 10.1179/146532811x12925735813841
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal tuberculosis: four cases and use of broncho‐alveolar lavage

Abstract: Despite the high prevalence of tuberculosis in adults and children, congenital and perinatal forms of tuberculosis are rare. Four patients with perinatal tuberculosis are described. Diagnosis was made by demonstration of acid-fast bacilli (AFB) on broncho-alveolar lavage (BAL) specimens (two cases), gastric aspirate smear (one case) and lymph node fine-needle aspirate (one case). All of the above specimens were subsequently positive on culture. Two infants died of progressive pulmonary failure, and one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…Tuberculin skin testing is positive in less than 15% of cases of congenital TB while gastric or tracheal aspirates are positive for TB in 80% of cases. A recent report proved the value of bronchoalveolar lavage as a technique of isolating the mycobacteria in perinatal TB [21]. Liver biopsy is really possible because it can have a very high diagnosis sensibility, which is 100% [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuberculin skin testing is positive in less than 15% of cases of congenital TB while gastric or tracheal aspirates are positive for TB in 80% of cases. A recent report proved the value of bronchoalveolar lavage as a technique of isolating the mycobacteria in perinatal TB [21]. Liver biopsy is really possible because it can have a very high diagnosis sensibility, which is 100% [25].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, bronchoalveolar lavage (BAL) is an imperative examination, because discovery of Mycobacterium tuberculosis DNA in BAL fluid by polymerase chain reaction (PCR) is an efficient method, for diagnosis in newborn [21]. Liver or lymph node biopsy may be undertaken for histology and culture but it remains highly invasive method for neonate.…”
Section: Methodsmentioning
confidence: 99%
“…Otras características clínicas pueden incluir lesiones de la piel, convulsiones, ictericia, otorrea, anomalías hematológicas y ascitis, que al imitar un proceso infeccioso retrasan el diagnóstico. Sin embargo, ante la pobre respuesta a los antibióticos y a la terapia de apoyo debe considerarse TB 2,12,13 .…”
Section: Discussionunclassified
“…1,6,11,12,19 All of the possible biological samples should be analyzed on slides for the search of alcohol/acid-fast bacilli and sent for culture. Neonatal gastric fluid is easy and rapid to collect, and provides good results; the sample should be collected in the morning before feeding.…”
Section: How To Diagnose Neonatal Tbmentioning
confidence: 99%
“…Other samples include tracheal aspirates, broncoalveolar lavage fluid, cerebrospinal fluid, ascitic fluid and, depending on the sites involved, biopsy of the skin, lymph nodes, bone marrow or liver. 1,6,11,12,19 In a recent analysis of 170 cases of congenital TB, although laboratory results were available in a minority of patients, Peng et al 3 found that the hemochromocytometric alterations observed during the course of TB in the first months of life are different from those encountered in older patients. Anemia (hemoglobin o10 g dl − 1 ), leukocytosis (white blood cell count ⩾ 12 000 μl − 1 ), Strength of recommendation A The panel strongly supports a recommendation for use.…”
Section: How To Diagnose Neonatal Tbmentioning
confidence: 99%